2016
DOI: 10.1007/s00106-016-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracochleäre Medikamentenapplikation in Verbindung mit Cochleaimplantaten

Abstract: Local drug application to the inner ear offers a number of advantages over systemic delivery. Local drug therapy currently encompasses extracochlear administration (intratympanic injection); intracochlear administration, particularly for gene and stem cell therapy; as well as various combinations with auditory neurosensory prostheses, either evaluated in preclinical or clinical studies, or off-label. To improve rehabilitation with cochlear implants (CI), one focus is the development of drug-releasing electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
2
0
2
Order By: Relevance
“…Coating electrodes with dexamethasone significantly reduces the hearing loss caused by insertion trauma [135][136][137], limits fibrotic scars, and avoids electrical impedance increases [136,138]. In one pilot study, the safety of dexamethasone-eluting electrodes was demonstrated in a small patient group, and lower impedances were measured among the group of patients with dexamethasone-eluting cochlear implant electrodes [139].…”
Section: Future Directionsmentioning
confidence: 99%
“…Coating electrodes with dexamethasone significantly reduces the hearing loss caused by insertion trauma [135][136][137], limits fibrotic scars, and avoids electrical impedance increases [136,138]. In one pilot study, the safety of dexamethasone-eluting electrodes was demonstrated in a small patient group, and lower impedances were measured among the group of patients with dexamethasone-eluting cochlear implant electrodes [139].…”
Section: Future Directionsmentioning
confidence: 99%
“…Die rationale Grundlage für die Behandlung akuter cochleo-vestibulärer Störungen mit Kortikosteroiden ist aufgrund Ihrer Wirkung an den im Innenohr vorhandenen Glukokortikoid-und Mineralokortikoidrezeptoren gegeben [76]. Die protektive Wirkung von Kortikosteroiden konnte in Tiermodellen für verschiedene Traumata gezeigt werden: 1) akutes akustisches Trauma [77][78][79][80][81], 2) Aminoglykosidund Cisplatin-Ototoxizität [82,83], 3) Pneumokokken-Meningitis [84], 4) Autoimmunassoziierter Hörverlust [85,86], 5) Insertionstrauma bei CI-Implantation (Übersicht in: [87]).…”
Section: Kortikosteroideunclassified
“…Die Hauptindikationen betreffen die akute idiopathische sensorineurale Hörminderung ("Hörsturz"), Morbus Menière und Tinnitus. Aber auch weitere Indikationen sind im Fokus der präklinischen und klinischen Forschung [87,103].…”
Section: Lokale (Intratympanale) Therapieunclassified
“…[1][2][3]. Implantable devices have actually been used since the 1950s, when the first pacemaker was used to restore a normal heart rate by continuously pulsing only the ventricle [4]; then the evolution of implantable technology began leading to most recent implants such as Ocular and Cochlear implants [5][6][7]. Although biomedical implants do have great importance in advancing healthcare, they often require some expertise or a skilled technician to operate.…”
Section: Introductionmentioning
confidence: 99%